Synthesis of (Z)-5-[(5-(2-(Phenylsulfonyl-ethyl)-1H-indol-3-yl)methelene]thiozolidine-2,4-dione of Potential Pharmacological Interest - Laxminarayana, Keetha; Rajendiran, Chinnapillai; Mukkanti, Khagga (Asian Journal of Chemistry, 2012)
Formylation of 5-bromoindole (1) under Vilsmeier-Hack formylation conditions using POCl3 and DMF as a reagents under cooling conditions (0-5 ºC) followed by simple processing gave a 5-bromoindole-3-carboxyaldehyde (2) and condensation of (2) with thiazolidine-2,4-dione (3) in toluene as a solvent in the presence of PTSA and TBAB as a phase transfer catalyst under stirring at room temperature for 10-30 min, then slowly raise the temperature to 105 ºC and maintained for 12-15 h, obtained a product(Z)-5-((5-bromo-1-alkyl-1H-indol-3-yl)methylene)thiazolidine-2,4-dione (4) later on condensation of (4) with phenylvinylsulfone (5) in the presence of palladium acetate as a catalyst in DMF as a solvent heating at 100-105 ºC for 16 h gave (5Z)-5-((1-alkyl-5-((E)-2(-(phenylsulfonyl)vinyl)-1H-indol-3-yl)methelene)thiozolidine-2,4-dione (8) and on reduction of (8) in the presence of hydrogen gas, palladium-carbon by using catalytic amount acetic acid medium in methanol as a solvent heating at 45-50 ºC for 8 h gave (Z)-5-((1-alkyl-5-(2-(-(phenylsulfonyl)ethyl)-1H-indol-3yl)methelene)thiozolidine-2,4-dione (11) and 11 could also be prepared by alternate methods structure of 11 has been established on the basis of its spectral and analytical data.